Transforming Vocational Education Management Towards Link and Match with Industry 4.0 - Slamed Riyanto; Sisilia Silifensi Sidok; Siti Ariah; Irpan Hasanudin (International Journal Labs, 2025)
The Fourth Industrial Revolution has driven the transformation of vocational education systems to meet the demands of a digital, technology-based workforce and 21st-century competencies. This study aims to analyze how the transformation of vocational education management in Indonesia can achieve an effective link and match with Industry 4.0. The research employed a descriptive qualitative approach through case studies in selected vocational institutions. Data collection techniques included in-depth interviews, participatory observations, and document analysis. The findings reveal that the main challenges include non-adaptive curricula, limited digital infrastructure, and low teacher capacity in industrial technologies. However, industry-based learning models such as teaching factories, hybrid training programs, and the application of digital technologies like Learning Management Systems (LMS) and Enterprise Resource Planning (ERP) systems have proven effective in improving graduates’ job readiness. A case study at SMK Negeri 1 Sidoarjo illustrates that pentahelix collaboration involving schools, industries, local governments, higher education institutions, and communities can foster a responsive and innovative vocational education ecosystem. The implications of this study highlight the urgency of managerial reform, strengthening strategic partnerships, and embracing digitalization in vocational education to produce graduates who are both relevant and competitive in the Industry 4.0 era.